The <Three Cs> of Japan’s Pandemic Response as an Ideograph - Allgayer, Sasha; Kanemoto, Emi (Frontiers in Communication, 2021)
While the COVID-19 pandemic soared across the world and changed the political dynamics on a global scale, Japan was viewed by some news sources as a “miracle” exception that beat the anticipated projections by experts of how the virus would affect the nation. Though there are a number of potential guesses about Japan’s initial pandemic outcome, which include low numbers of testing, an existing culture of mask-wearing, sanitation, and certain degree of social distancing, the political environment and communication from the government have also been accredited to the so-called “success” of Japan’s pandemic experience. By using the concept of ideograph, this study rhetorically analyzes the key slogan that emerged from Japanese political discourse surrounding the COVID-19 situation: 3つの密 - Mittsu no Mitsu [The Three Cs]. Specifically, the authors conclude the ways in which